Effectiveness of different methods for the extraction of principle actives and phytochemicals content in medicinal herbals - Lima, Nerilson M.; Falcoski, Thais O. [UNESP]; Silveira, Romena S.; Vieira, Haustin S.; Santos, Vanessa N. C.; Ramos, Rhianne R.; Silva, Julio Cesar de P. [UNESP]; Andrade, Teresinha de Jesus A. dos S.; Carli, Alessandra E. P.; Costa, Paulo [UNESP]; La Porta, Felipe A.; Almeida, Mauro (Ms-editions, 2021)
In this present study, we investigated the influence of various extraction methods including maceration, sonication, infusion, decoction, and microwave extraction, on the chemical and biological potential of phytochemicals extracted from three medicinal plants (Ageratum conyzoides, Plantago major and Arctium lappa L). The results were subsequently analyzed by variance analysis. Our results suggested that sonication is the most effective extraction method among the five methods tested herein, for the extraction of phytochemicals that have a high antioxidant potential and high phenolic content. The three plants employed for this study had a high concentration of flavonoids and phenolics which was compatible with the chemosystematics of the species. All the samples possessed a Sun Protection Factor (SPF) of less than 6. Interestingly, a maximum reaction time of approximately 20 min was noted for the complexation of AlCl3 with the flavonoids present in the phytochemical extract during analyses of the kinetic parameters. We finally identified that the Ageratum conyzoides extract, prepared by sonication, possessed a significant pharmacological potential against hepatocarcinoma tumour cells, whose result can guide further studies for its therapeutic efficacy.
Keywords: Medicinal herbals; Ageratum conyzoides; Plantago major; Arctium lappa; Phytocompounds